The Value of Research Methods in Psychotherapy Research: A Reply to the Commentary of Dr Norton. (December 2015) - Strunk, Daniel R; Pfeifer, Benjamin J
Abstract : Norton's commentary on our article has prompted us to think further about the purpose of psychotherapy research. We agree with his suggestion that researchers have much work to do to understand when and for whom interventions are most efficacious. We hope that our field will make progress in this regard. In this reply, we further describe why we believe careful attention to research methods, such as those highlighted in our article, is key to making progress in psychotherapy research.